The Role of Entrepreneurial Approaches to Librarianship: Professional Development - J.Santhi; Loganayaki, R.; V.Swarnamugi (International Journal of Psychosocial Rehabilitation, 2020)
This paper provides how a librarian can act as an Entrepreneurial Approaches to develop professional skills in emerging technologies and subject specialties in today’s global environment. Librarian brings access to different sources of information and also forms a network among knowledge community. Library professionals have the potential to be called as good entrepreneurs as they look for the needs of their users and fulfill them. This paper gives some professional development and entrepreneurial approaches to librarianship.